Epithelial ovarian tumors Analysis of the value of surgery and treatments platinic in a population of 118 cases - Viola, Alberto; Signorelli, Silvana; Ferrari, araceli; Alonso, Isabel; Barrios, Enrique; Sabini, Graciela; Musé, Ignacio (Cirugía del Uruguay, 2000)
Between 1984 and 1994, 118 epithelium ovarían tumours were studied, of which 22 stage / patients {19,3%), 26 stage 11 patients {27,8%), 53 stage 1/1 patients (46,5%), and 13 stage IV patients (11,4%). The mean age was 58 years (range, 14 to 89 years). Histo!ogica!ly, forms found were as fo!low: 84 serous cystomas (71,2%), 14 mucinous cystomas (11,9%), 8 endometrioid tumors, and 7 clear ce!/ tumors.